1999
DOI: 10.1096/fasebj.13.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐induced internalization of CD38 results in intracellular Ca2+mobilization: role of NAD+transport across cell membranes

Abstract: CD38, a transmembrane glycoprotein widely expressed in vertebrate cells, is a bifunctional ectoenzyme catalyzing the synthesis and hydrolysis of cyclic ADP-ribose (cADPR). cADPR is a universal second messenger that releases calcium from intracellular stores. Since cADPR is generated by CD38 at the outer surface of many cells, where it acts intracellularly, increasing attention is paid to addressing this topological paradox. Recently, we demonstrated that CD38 is a catalytically active, unidirectional transmemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
124
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 42 publications
10
124
0
3
Order By: Relevance
“…; and (2) how does CD38, whose short intracellular domain lacks consensus sequences, cross-talk with its partners such as BCR? Related to the first question, the groups of De Flora [8] and Lee [9], based on experimental and structural data, have suggested that CD38 could function as a channel\transporter for catalytically formed cADPR leading to increased intracellular Ca# + levels. However, Lund et al [10] have shown that CD38 signalling in B-cells was independent from its catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…; and (2) how does CD38, whose short intracellular domain lacks consensus sequences, cross-talk with its partners such as BCR? Related to the first question, the groups of De Flora [8] and Lee [9], based on experimental and structural data, have suggested that CD38 could function as a channel\transporter for catalytically formed cADPR leading to increased intracellular Ca# + levels. However, Lund et al [10] have shown that CD38 signalling in B-cells was independent from its catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…These mediate the export of "de novo" synthesized CD38 to the plasma membrane (16) and also the opposite process of CD38 endocytosis that is observed upon incubating several cells types with specific ligands, e.g. 18). In both cases, the active site of CD38 is intravesicular and therefore unavailable to cytosolic NAD ϩ .…”
mentioning
confidence: 99%
“…This "topological paradox" of the CD38/cADPR system appeared to be challenging, in view of the powerful calcium releasing activity of cADPR and of the remarkably increased cytosolic calcium ([Ca 2ϩ ] i ) levels (and consequent triggering of calcium-stimulated cell functions) that are observed during both de novo expression of CD38 (16) and its ligand-induced internalization (18). Both findings clearly indicated, in the absence of obvious underlying mechanisms, that intracellularly localized CD38 (e.g.…”
mentioning
confidence: 99%
“…The concentrations of all potential V factors (a collective term for NAD, NMN, and NR) in human body fluids are not known precisely. Although in certain microenvironments, NAD concentrations in the low micromolar range can be reached, an average NAD serum concentration of 50-60 nm has been reported (Zocchi et al, 1999). The NAD concentrations in extracellular body fluids of pigs are between 0.2 and 1 μm (O' Reilly and Niven, 2003).…”
Section: Ligand Bindingmentioning
confidence: 99%